Development Of The “Rumah Pintar Gembira (Maharia)” Learning Media To Improve Cognitive Abilities Of Early Childhood - Nura Puspa Nirwani; Brigita Puridawaty; Debie Susanti (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to develop an innovative learning medium called Rumah Pintar Gembira (MAHARIA) to improve the cognitive abilities of early childhood. The research was conducted using a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was carried out in two early childhood education institutions, namely TK Sukakarya and TK Cemerlang in Sukabumi City, with children aged 4–5 years as the research subjects. The needs analysis revealed that cognitive learning media used in both institutions were limited and mostly consisted of worksheets and static picture cards. Most teachers (78–90%) expressed the need for concrete, manipulative, and interactive learning media, while the average cognitive ability of children was still in the low category (43.7%). Based on these findings, the MAHARIA learning media was developed in the form of a three-dimensional miniature house equipped with eight learning activity components designed to stimulate number recognition, one-to-one correspondence, classification skills, and simple problem-solving abilities. The feasibility of the media was validated by three experts consisting of one media expert and two material experts, resulting in an average feasibility score of 75.3%, categorized as feasible with revision. The effectiveness test was conducted using a comparative experimental design. The experimental group obtained an average N-Gain score of 0.51 (moderate category), which was higher than the comparison group with an average N-Gain score of 0.28 (low category). These findings indicate that the MAHARIA learning media contributes positively to improving early childhood cognitive abilities compared to conventional learning media. Therefore, the MAHARIA learning media can serve as an alternative innovative learning medium to support cognitive development in early childhood education.